2022
DOI: 10.1021/acsaem.2c00860
|View full text |Cite
|
Sign up to set email alerts
|

ZnO–CoO Composite Nanosphere Array-Modified Carbon Cloth for Low-Voltage Hysteresis Li Metal Anodes

Abstract: Li metal anodes possess the largest energy density among all anode candidates, while dendrite growth is a huge barrier for its application. Herein, carbon cloth modified with ZnO–CoO particles is synthesized as a host for Li metal anodes (Li-ZnO–CoO/CC). During plating, Li tends to first fill the inside space of the Li-ZnO–CoO/CC, while in stripping, Li will be stripped from the surface. In addition, the three-dimensional (3D) structure could enable an internal space for Li deposition and alleviate Li volume e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…22,28 Meanwhile, the lithiophilic ZnO facilitates the uniform Li nucleation and increases the lateral Li atom diffusion rate. [29][30][31] Due to the synergistic effect between BP and ZnO, uniform Li deposition is achieved. Consequently, Li metal anodes with the ZnO@BP nanosheet coating (ZnO@BP/Li) exhibit enhanced interface kinetics and excellent cycling performances in symmetric cells.…”
Section: Introductionmentioning
confidence: 99%
“…22,28 Meanwhile, the lithiophilic ZnO facilitates the uniform Li nucleation and increases the lateral Li atom diffusion rate. [29][30][31] Due to the synergistic effect between BP and ZnO, uniform Li deposition is achieved. Consequently, Li metal anodes with the ZnO@BP nanosheet coating (ZnO@BP/Li) exhibit enhanced interface kinetics and excellent cycling performances in symmetric cells.…”
Section: Introductionmentioning
confidence: 99%
“…For decades, green chemistry, energy regeneration, and other energy issues have been a problem that all researchers have been trying to solve. Over the years, the large amount of primary energy inputs has led to a gradual increase in the proportion of global pollution, along with the depletion of nonrenewable energy problems, so there is an urgent need for secondary energy technology that can be used as a substitute. According to literature research, zinc-air batteries have great potential as a secondary energy technology because of their huge theoretical energy. Although it has great potential, the slow kinetics of the oxygen reduction and oxygen precipitation reactions during the charging and discharging process of zinc-air batteries lead to low cycle efficiency, which prevents the batteries from being used on a large scale. Pt-based noble metals are considered to be the ideal catalysts for zinc-air batteries, but due to their scarcity, they are not available for large-scale applications due to their high cost. Therefore, according to the literature, it was found that in recent years, many researchers have done a lot of work on the nonprecious metal catalysts used, such as doped transition metal oxides, synthesized MOFs and COFs, carbon-based materials containing metals, and so on, in place of precious metals. Although a lot of beautiful work has been done and quite high performance has been shown, it is still not up to the desired level.…”
Section: Introductionmentioning
confidence: 99%
“…Targeting the above issues, many strategies have been pursued over the past several years, including establishing artificial SEI, optimizing electrolyte additives, using solid electrolytes, modifying spectators, inserting 3D scaffolds, , and so forth.…”
Section: Introductionmentioning
confidence: 99%
“…5−9 However, challenges like hazardous volume expansion and fatal dendrite/mossy lithium growth are prone to cause a severe decay of Coulombic efficiency (CE), increased overpotential, and internal shorting, dragging lithium metal anodes out of commercialization. 1,10,11 Targeting the above issues, many strategies have been pursued over the past several years, including establishing artificial SEI, 12−14 optimizing electrolyte additives, 15 using solid electrolytes, 16 modifying spectators, 17 inserting 3D scaffolds, 18,19 and so forth. "Sand's time" model describes the initiation of dendrite nucleation that occurs when the current density comes up to over-limiting current and decreasing current density could suppress the dendrite and mossy Li formation.…”
Section: ■ Introductionmentioning
confidence: 99%